Identification and function analysis of two fibroblast growth factor receptor (FGFR) from Scylla paramamosain: The evidence of FGFR involved in innate immunity in crustacean. Issue 131 (December 2022) - Li, Bing-Wu; Xu, Wen-Bin; Dong, Wei-Ren; Zhang, Yan-Mei; Cheng, Yuan-Xin; Chen, Da-Yong; Xiao, Yi; Chen, Yu-Yin; Shu, Miao-An
Abstract: The fibroblast growth factor receptor (FGFR) belongs to the tyrosine kinase family consisting of four members ( FGFR1-4 ). This study involved identification and characterization of FGFR1 and FGFR3 from mud crab Scylla paramamosain for the first time. The obtained cDNAs of SpFGFR1 and SpFGFR3 were 2, 380 bp and 2, 982 bp in length with a 1, 503 bp and 2, 310 bp open reading frame, respectively. The predicted Sp FGFR1 protein included three immunoglobulin domains and a transmembrane region, while SpFGFR3 protein possessed a typical TyrKc (Tyrosine kinase, catalytic) domain. Real-time PCR analysis showed that SpFGFR1 and SpFGFR3 were highly expressed in the hepatopancreas. Furthermore, the expression levels of SpFGFR1 and SpFGFR3 in the hepatopancreas were enhanced following challenges with Vibro alginolyticus, Staphylococcus aureus, Poly (I:C) and White spot syndrome virus, which shows the involvement of SpFGFR1 and SpFGFR3 in innate immune response to infections from bacteria and virus. There was significant suppression of six antimicrobial peptide genes ( SpALF1-5 and SpCrustin ) and three NF-κB members ( SpDorsal, SpIKK and SpRelish ) when SpFGFR1 and SpFGFR3 was interfered in vivo . Also, treatment of the hemocytes with specific inhibitor of Sp FGFR for 24 h consistently down-regulated SpDorsal, SpRelish and AMPs. These results suggested that SpFGFR1 and SpFGFR3 played important roles in regulating the Toll signaling pathway and immune deficiency (IMD) pathway through NF-κB signaling pathway. These findings may provide new insights into the role of FGFR s in the innate immune function of crustaceans. Highlights: The SpFGFR1, SpFGFR3 genes were firstly identified and characterized. FGFR existed in crab and responded to bacterial and viral infection. FGFR regulated expressions of antimicrobial peptides genes in S. paramamosain.